Bloody November internet shutdown (Iran) - Voidly (Voidly Global Censorship Index, 2019)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2019-0001. Severity: critical. Confidence: 90%